Records Committee review for rare bird sighting of Lesser Black-backed Gull at Davenport, 1991 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1991)
Records Committee review for a Lesser Black-backed Gull at Davenport in Scott County, IA on January 16, 1991. Includes a record review document with votes, an article in Iowa Bird Life, comparisons of different gull sightings, and a documentation form submitted to the committee. Epson - sheet feed